Correlation of Ki-67 Expression with the Stage of Disease in Patients of Colorectal Carcinoma - Ashutosh Nagpal; Poras Chaudhary (Prague Medical Report)
Colorectal carcinoma (CRC) is a multifactorial disease process with several factors influencing prognosis. CRC is associated with the expression of multiple cell proliferating markers such as Ki-67/MIB-1. This study was aimed to examine possible correlations between Ki-67 expression and the stage of colorectal carcinoma. This was a single centre prospective study including 93 patients who underwent surgery for colorectal carcinoma. Expression of Ki-67 was assessed by immunohistochemistry on formalin-fixed paraffin-embedded tumour tissue blocks. Categorical variables data were presented as number with corresponding percentage. Continuous data were analysed using parametric tests as applicable and categorical data using nonparametric tests. The level of significance α = 0.05 and P-value < 0.05 was considered statistically significant. The average Ki-67 expression was 77.66% (SD [standard deviation] = 9.68%) with a range of 60 to 90%. Patients with nodal involvement and larger size had a higher Ki-67 expression. To assess statistical significance, the cut-off for Ki-67 expression was set at 70%. Of 66, 48 (72.7%) adenocarcinomas and 12/18 (66.66%) mucinous adenocarcinomas had Ki-67 expression above cut-off as compared to signet ring cell variety. Ki-67 expression in colorectal carcinoma signifies mitotic activity of the tumour. Thus, it could be used as an adjunct to the existing diagnostic arsenal to help overcome its limitation in gauging the functional status of tissues.